Warum der Freihandel fertig hat - Martin Braml; Gabriel Felbermayr (Wirtschaftsdienst, 2024)
The era of free trade seems to be over. Increasing protectionism and new or intensified trade wars are to be expected at the latest with the new administration of President-elect Donald Trump. Tariff threats and geopolitical conflicts are focussing attention on the issue of (supply) security. Political efforts are being made to diversify supply chains and shift the production of critical goods to the domestic market. The vision of prosperity-enhancing free trade and democracy-promoting 'change through trade' appears to be overshadowed by a paradigm of free trade as a zero-sum game. The contributions discuss what effects these developments may have on the export-orientated German economy and what measures Germany and the EU should take in this mixed situation.
Keywords: F13; F52; F53; 330